2016
DOI: 10.3310/hsdr04050
|View full text |Cite
|
Sign up to set email alerts
|

Cross-national comparative mixed-methods case study of recovery-focused mental health care planning and co-ordination: Collaborative Care Planning Project (COCAPP)

Abstract: BackgroundConcerns about fragmented community mental health care have led to the development of the care programme approach in England and care and treatment planning in Wales. These systems require those people receiving mental health services to have a care co-ordinator, a written care plan and regular reviews of their care. Care planning and co-ordination should be recovery-focused and personalised, with people taking more control over their own support and treatment.Objective(s)We aimed to obtain the views… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(71 citation statements)
references
References 91 publications
1
69
0
1
Order By: Relevance
“…The only challenge came from Abby who reported she had seen patients asked about their feelings in a ward round. However, recent research indicates that there is insufficient service user involvement occurring in care planning (Grundy et al, 2016;Simpson et al, 2016b). Findings from my study suggest student participants' views are clear that elements of service user involvement in care planning are not widely evident.…”
Section: Jtmentioning
confidence: 71%
See 4 more Smart Citations
“…The only challenge came from Abby who reported she had seen patients asked about their feelings in a ward round. However, recent research indicates that there is insufficient service user involvement occurring in care planning (Grundy et al, 2016;Simpson et al, 2016b). Findings from my study suggest student participants' views are clear that elements of service user involvement in care planning are not widely evident.…”
Section: Jtmentioning
confidence: 71%
“…However, users have reported that limited collaboration has been the reality (Newman et al, 2015). Interestingly, research in the area of personalised, recovery focused care planning in mental health is under-developed (Simpson et al, 2016b), with limited peerreviewed articles in the mental health nursing literature in this area. The participants referred to in this section provided accounts that suggest the activity of involving users in care planning occurs seldom, and that nurses have limited skill and confidence regarding how to accomplish such activity.…”
Section: "Some People When They're Doing Their Care Plan Reviews Won'mentioning
confidence: 99%
See 3 more Smart Citations